G-Form as a for Collecting Student Assignments during Online Learning - Widiyaningsih, Wiwin Widiyaningsih; MASKUROH, AULIYA MASKUROH; Rifai, Muh Husyain (Universitas Veteran Bangun Nusantara, 2021)
The Covid-19 pandemic has caused changes in all aspects of life, one of which is the education system. Changes in the education system make it difficult for students to receive material because learning that is usually done conventionally turns into distance learning or is done online. Its implementation cannot be separated from the use of information technology. So that students and teachers are required to be able to operate all online learning media such as Google Classroom, Google Forms, Google Meet. In online assignments, students have obstacles in terms of collecting online-based assignments, but students are required to collect evidence of work results to school so that it has an impact on the assessment and grades of student assignments. The purpose of this article is to solve the problem of collecting student assignments during online learning. This study uses a descriptive qualitative method by paying attention to the collection of student assignments during online learning through the G-Form (Google Form). Based on the results of the study, it can be concluded that using the g-form as a solution in collecting online learning assignments at SMA Negeri 1 Nguter Sukoharjo.